The influence of France on sports in the Kingdom of Serbia - Gavrilović, Dejan (Napredak, 2025)
During its struggle for independence in the 19th century, Serbia considered physical culture primarily through the soldiers’ skills or the preparation of future soldiers. It is because of these reasons that military structures had a dominant influence on the introduction and development of physical exercise until the Great War.Gained independence and promoting the principality to the rank of the kingdom encouraged Serbian society to make significant changes in different social spheres. Physical culture also experienced positive changes after the 1880s. With the arrival of Charles Doucet, a Belgian fencing instructor, in Serbia at the end of the 19th century, Serbian society was introduced to the French fencing method. Doucet’s pupils promoted the fencing sport in the Kingdom of Serbia, as well as subsequently in the Kingdom of Yugoslavia. At the beginning of the 20th century, with the aim of specializing in physical culture, Officer Dragomir Nikolajević was sent to France, to Joinville School of Physical Education. After his return from schooling, Nikolajević worked on the development of the Sokol movement and the Olympic movement. By accepting Baron de Coubertin’s ideas, the Kingdom of Serbia ranked among few countries which introduced Olympism before the Great War. The influence of France at the beginning of sports in the Kingdom of Serbia was the foundation for further development of physical culture in the territory of the Republic of Serbia and in the region on the whole.
Keywords: France; Kingdom of Serbia; sport; Joinville School (École de Joinville); Dragomir Nikolajević